Sustainability for lower risk: examining ESG scores as indicators of credit risk in African firms - Malandu, Vimbai Melissa (Graduate School of Business (GSB), 2025)
In light of the growing consideration of Environmental, Social, and Governance (ESG) metrics in credit appraisal, this study investigates the relationship between ESG performance and credit risk for African firms from 2012 to 2022. Using Refinitiv ESG scores and Altman's Z”-score as the primary credit risk measure, this analysis employs OLS, fixed effects, random effects, instrumental variables, and GMM estimations. While the combined ESG score shows no significant relationship with credit risk, the study makes original contributions as one of the first African emerging market studies to examine ESG as a non-financial credit risk determinant. It uniquely applies a multi-model econometric approach and combines multiple credit risk proxies, including the National University of Singapore Credit Research Initiative's Probability of Default. This triangulation enhances analytical robustness and contributes to the empirical foundation for ESG-credit risk research in emerging markets. Accounting for endogeneity through GMM, the Governance pillar shows a short-term, significant negative impact on credit risk, indicating governance's time-sensitive role in creditworthiness. The Environmental and Social pillars show no significant impact, with mixed results in static models, highlighting sensitivity to model selection. Industry-specific analysis reveals no significant relationship between aggregated ESG scores and default risk. However, the Environmental pillar positively impacts credit risk in Industrials, while Governance negatively impacts credit risk in Basic Materials. No significant ESG effects are found in Consumer Staples, Consumer Discretionary, or Real Estate sectors. The study is limited by constrained ESG data coverage for African firms, reflecting broader challenges in ESG reporting across the continent. These findings emphasise the need for mandatory, standardised ESG disclosures to enable nuanced credit risk assessments, critical for African markets where development capital and effective risk management frameworks are in high demand.